Educational Dialogue as a Basic Concept of Developing Paradigms in Modern Education - V. Vykhrushch; L. Romanyshyna (Pedagogical Discourse, 2016)
Dialogic technologies, their scientific development and research are key issues of educational system modernization. A holistic understanding of the nature of dialogue system of human knowledge is a problem of linguistics, rhetoric, literary criticism, philosophy, psychology and pedagogy. The acquisition of dialogical learning technologies in modern educational practice is complicated by inconsistency of philosophical, linguistic and psychological interpretations of the phenomenon of «dialogue».The use of dialogue in education due to the methodological difficulties: lack of generally accepted interpretation of the term «dialogue», incompleteness general theory of dialogue and focus of education on different cultural values of the dialogue. The concept of «educational dialogue»  is designed to ensure the change in mass of pedagogical influence by modern teacher. Theoretical sources most philosophical concepts of dialogue are the theory of human knowledge and consciousness research, age patterns of development, peculiarities of educational process at different age stages. The practice-oriented psychological concepts of dialogue  is based on the idea of unity of knowledge and communication.Culture of dialogue relations is due to the national humanitarian tendencies of development national higher education. Dialogue is not a specific methodological procedure but the method of constructing partnerships in learning. It is characterized by the following features: this is the process of developing new information, common to the communicants and the birth of their community; the uniqueness of each partner and their fundamental equality in situations of the various and original points of view; each orientation to understanding and active interpretation of its terms by partner; waiting for a response and its prediction in own utterance; mutual complementarity positions of participants in communication; use the experience of the participants during their interaction.Dialogical educational communication is the central element of the learning process. Educational dialogue - subjective exchange of knowledge, experiences, and ways of meanings – according to its content is interpersonal interaction, which aims to change attitudes and style of activity of its members. Psychological factors of teachers professional development of their activities in training is the change from monologue to professional dialog.